Topological guided-mode resonances: basic theory, experiments, and applications - Choi Yu Sung; Park Chan Young; An Soo-Chan; Pyo Jung Hyeon; Yoon Jae Woong (Nanophotonics)
Guided-mode resonance (GMR) is a key principle for various nanophotonic elements in practice. In parallel, GMR structures offer an efficient experimental platform for fundamental study of novel wave phenomena because of its versatile capability to synthesize complicated potential distributions and analyze deep internal properties conveniently in the optical far-fields. In this paper, we provide a brief review of topological GMR effects as a promising subtopic of the emerging topological photonics. Starting from a conceptually minimal model, we explain basic topological parameters, associated optical properties, experimental realizations, and potential applications. We treat topics of recent interest including topological edge-state resonances, deterministic beam shaping and mode matching, bound states in the continuum, unidirectional resonances, and polarization vortices. We finally address limitations, remaining challenges, and perspective of the topic.